Security Analysis Combination Secret Sharing Protocol and Three-Pass Protocol. (March 2019) - Nababan, Darsono; Rahim, Robbi
Abstract: Protocols Secret Sharing is a method used to divide or break a secret message to 2 (two) or more recipients so that another beneficiary cannot know the results of fractional shares, except each recipient to exchange shares for reconstructing the secret. The problem that occurs is when the process transfer of shares, there are others who know the shares of the recipients and then that party is also able to reconstruct the secret, therefore the secret message required additional security, such as encryption of the message. The protocol used are the Three-Pass, this algorithm will guarantee the exchange of shares between the recipients. The three-pass protocol also provides convenience to the recipient to secure distribution share without having to do the encryption key, and the encrypted share is still safe. This study analyzes the security of secret delivery by combining the Secret Sharing Protocol and the Protocol Three-Pass.